Periodisation in professional tennis: A macro to micro analysis of load management strategies within a cluttered calendar. Issue 3 (June 2023) - Perri, Thomas; Duffield, Rob; Murphy, Alistair; Mabon, Tom; Reid, Machar
Aim: This study analysed the periodisation of internal loads across training and competition blocks of future top 250 (T250) professionally ranked tennis players' professional transitions. Methods: Retrospective data was analysed from 10 male and 8 female Australian tennis players aged between 16 to 18 who later achieved professional rankings inside the T250. Session-rating of perceived exertion training load (sRPE TL) was collected from all sessions using an online application. Data were collected from official matches, on-court skill-based training, and off-court sessions (i.e., strength, conditioning, body management) and classified according to their occurrence in either training or competition blocks. Weekly sRPE TL was quantified for respective training and competition periods. One-way analysis of variance and effect size analyses compared within-sex training loads between training and competition blocks. Results: Training blocks lasted longer than competitions for both sexes ( p < 0.05). Training blocks for males had greater daily durations ( p < 0.01), but not sRPE TL ( p = 0.08). Total load for females was not different between periods ( p > 0.05). Training blocks had higher on-court and off-court loads compared to competition ( p < 0.05). No difference in weekly training and competition loads were observed ( p > 0.05). Skill-based sessions in training periods were longer with higher loads for both sexes ( p < 0.05), with no difference in duration, rating of perceived exertion (RPE) and sRPE TL observed between periods for off-court sessions ( p > 0.05). Conclusions: Future T250 players experience higher sRPE TL in training blocks, with reductions in both total on-court and off-court load during tournaments. Regardless, limited evidence of periodised weekly loads exists within training and competition periods.